High temperature oxidation of iron–iron oxide core–shell nanowires composed of iron nanoparticles. Issue 5 (14th January 2016) - Krajewski, M.; Brzozka, K.; Lin, W. S.; Lin, H. M.; Tokarczyk, M.; Borysiuk, J.; Kowalski, G.; Wasik, D.
Abstract : The thermal oxidation of iron nanowires causes their breakdown due to void coalescence and formation of α-Fe2 O3 microparticles and microrods. Abstract : This work describes an oxidation process of iron–iron oxide core–shell nanowires at temperatures between 100 °C and 800 °C. The studied nanomaterial was synthesized through a simple chemical reduction of iron trichloride in an external magnetic field under a constant flow of argon. The electron microscopy investigations allowed determining that the as-prepared nanowires were composed of self-assembled iron nanoparticles which were covered by a 3 nm thick oxide shell and separated from each other by a thin interface layer. Both these layers exhibited an amorphous or highly-disordered character which was traced by means of transmission electron microscopy and Mössbauer spectroscopy. The thermal oxidation was carried out under a constant flow of argon which contained the traces of oxygen. The first stage of process was related to slow transformations of amorphous Fe and amorphous iron oxides into crystalline phases and disappearance of interfaces between iron nanoparticles forming the studied nanomaterial (range: 25–300 °C). After that, the crystalline iron core and iron oxide shell became oxidized and signals for different compositions of iron oxide sheath were observed (range: 300–800 °C) using X-ray diffraction, Raman spectroscopy and Mössbauer spectroscopy. According to the thermal gravimetric analysis, the nanowires heated up to 800 °C under argon atmosphere gained 37% of mass with respect to their initial weight. The structure of the studied nanomaterial oxidized at 800 °C was mainly composed of α-Fe2 O3 (∼93%). Moreover, iron nanowires treated above 600 °C lost their wire-like shape due to their shrinkage and collapse caused by the void coalescence.